EFEKTIVITAS PENGGUNAAN BANTUAN OPERASIONAL SEKOLAH (BOS) PADA KEGIATAN PEMBELAJARAN DI SMPN 1 TANJUNGSAMAK KEC. RANGSANG KABUPATEN KEPULAUAN MERANTI - Elmizola, Fitriani; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Undang-Undang No. 20 tahun 2003 tentang Sistem Pendidikan Nasional mandates that every citizen over the age of 7-15 years are required to follow basic education. One of the efforts undertaken by the government in order to accelerate the achievement of nine-year compulsory education program is to promote Bantuan Operasional Sekolah (BOS) program. BOS is a government program that is basically the cost of funding for the provision of non prosonalia operating costs for basic education unit as the executor of compulsory education. One of the schools that received the BOS funds are SMPN1 Tanjungsamak, of the phenomenon is seen in the use of BOS at SMPN 1 Tanjungsamak there are still problems that the purpose of the BOS funds can not be achieved.This purpose of this research is to know the effectiveness use of BOS in the learning activities of students of SMPN 1 Tanjungsamak Kec. Rangsang Kabupaten Kepulauan Meranti and to know the factors that influence the effectiveness usage of BOS at SMPN 1 Tanjung samak learning activities. In this research, researchers used the theory of management, the effectiveness theory, and the theory of organizational effectiveness. Which is used as a measure is the theory of organizational effectiveness by Sondang P. Siagian.The research location was at SMPN 1 Tanjungsamak. The method used in this research is descriptive qualitative. Informants in this research is principals, school treasurer, school committees, school inspectors, head of administration, society, and students, with data collection techniques include observation and interviews. While the types and sources of data include the premiere of data is data obtained directly from the informant research includes interviews and observations and secondary data is the data obtained to supplement primary data obtained, which aims to support the research.Based on the results of research through interviews and observation is known that the effectiveness usage of BOS on learning activities of students at SMPN 1 Tanjungsamak Kec. Rangsang Kepulauan Meranti yet effective. This means there is still a problem in the use of the BOS, and the factors that influence the use of BOS in the learning activities of students of SMPN 1 Tanjungsamak Kec. Rangsang Kepulauan Meranti are socialization factors and control factors.Keyword : Effectiveness, BOS, Strategy